2021
DOI: 10.1038/s41416-021-01608-2
|View full text |Cite
|
Sign up to set email alerts
|

Once weekly selinexor, carfilzomib and dexamethasone in carfilzomib non-refractory multiple myeloma patients

Abstract: Background Proteasome inhibitors (PIs), including carfilzomib, potentiate the activity of selinexor, a novel, first-in-class, oral selective inhibitor of nuclear export (SINE) compound, in preclinical models of multiple myeloma (MM). Methods The safety, efficacy, maximum-tolerated dose (MTD) and recommended phase 2 dose (RP2D) of selinexor (80 or 100 mg) + carfilzomib (56 or 70 mg/m2) + dexamethasone (40 mg) (XKd) once weekly (QW) was evaluated in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
1
25
1
Order By: Relevance
“…Increasing data have been indicated that the MM is often accompanied by the multiple osteolytic lesions, hypercalcemia, or kidney damage ( 1 5 ). Although therapeutic approaches to MM have been rapidly evolving, and MM is typically sensitive to a variety of cytotoxic chemotherapies, the prognosis of patients with distal metastasis (the extra-bone MM, at an advanced stage of the disease) is still poor ( 4 6 ). Bone destruction is among the most debilitating manifestations of MM and results from the interaction between myeloma cells and the bone marrow microenvironment ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing data have been indicated that the MM is often accompanied by the multiple osteolytic lesions, hypercalcemia, or kidney damage ( 1 5 ). Although therapeutic approaches to MM have been rapidly evolving, and MM is typically sensitive to a variety of cytotoxic chemotherapies, the prognosis of patients with distal metastasis (the extra-bone MM, at an advanced stage of the disease) is still poor ( 4 6 ). Bone destruction is among the most debilitating manifestations of MM and results from the interaction between myeloma cells and the bone marrow microenvironment ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…XVd treatment in the BOSTON trial was initiated earlier in patients with less refractory MM (1–3 previous lines of therapy) and better overall health and resulted in significantly greater overall response rate and progression-free survival than in those treated with Vd. A recent expert review concluded that selinexor holds potential for being used in combination with highly active triplets in newly diagnosed multiple myeloma, based in part on the favorable response rates in the STOMP [ 9 ] and BOSTON trials [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of such a regimen was rather challenging at the beginning of its development with frequent Grade ≥3 thrombocytopenia, anaemia, hyponatraemia, fatigue, and gastrointestinal toxicity. Subsequent studies have used less frequent dosing of selinexor (weekly instead of twice per week) in combination with bortezomib, 66 carfilzomib 41 or pomalidomide, 67 showing a more favourable toxicity profile. We believe weekly doses of selinexor to be a reasonable option in TCR patients, and it should be combined with weekly carfilzomib in patients with non‐carfilzomib refractory MM or with pomalidomide in non‐pomalidomide refractory MM 67 .…”
Section: Treatment Optionsmentioning
confidence: 99%
“…We believe that given the dismal prognosis of TCR MM, the lack of a clearly superior and widely available therapy, and the absence of high-level evidence in this setting, it is imperative to offer such patients enrolment in therapeutic clinical trials whenever possible. Here we summarise clinical data on different drugs, combinations and approaches (Table 1) [35][36][37][38][39][40][41][42][43][44][45][46] employed in this setting and suggest an algorithm to guide choice of therapy (Figure 1).…”
Section: Tr E Atm E N T Op Tionsmentioning
confidence: 99%